Bladder dysfunction does not affect long‐term success rate of the retropubic suburethral sling procedure in women with stress urinary incontinence. Issue 2 (28th November 2018) - Ong, Hueih Ling; Kuo, Hann‐Chorng
Abstract : Objective: This study investigated the long‐term success rate of retropubic suburethral sling in the treatment of women with stress urinary incontinence (SUI) and different bladder function. Methods: Surgical outcomes of women with SUI undergoing a retropubic suburethral sling procedure between October 1989 and November 2014 were analyzed retrospectively. Bladder function was evaluated in every patient preoperatively using videourodynamic studies. Patients were classified as having stable bladder, detrusor overactivity (DO), or detrusor underactivity (DU). Baseline urodynamic parameters were analyzed and long‐term therapeutic outcomes were compared among these three groups. Results: In all, 403 patients underwent sling procedure for SUI. Of these, 291 (72.2%) had a stable bladder, 78 (19.4%) had DO, and 34 (8.4%) had DU. Mean (± SD) patient age was 60.2 ± 11.8 years, and the median follow‐up was 97 months (interquartile range 24–325 months). Postoperatively, the overall continence rate was 83.4% (336/403). After surgery, 71 patients (17.6%) complained of dysuria, 14 (3.5%) complained of urgency incontinence, 25 (6.2%) had recurrent SUI requiring a secondary sling procedure, and urethrolysis was performed in 13 (3.2%). In the stable bladder, DO, and DU groups, the 5‐year continence rates were 88.6%, 84.1%, and 79.4%, respectively ( P = 0.59), whereas the 10‐year continence rates were 83.8%, 72.9%, and 79.4%, respectively. Kaplan–Meier survival analysis indicated that the long‐term success rate was similar among the three groups ( P = 0.39). Conclusions: The overall continence rate was 83.4% and the 10‐year continence rate was satisfactory in all bladder function subgroups. Treatment outcomes were the same for women with SUI but different bladder function.